PROFIL KECERDASAN EMOSIONAL SISWA - Nabilah Farah; Sunarya Yaya; Suherman Suherman (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2020)
This research aimed to find the representation of emotional intelegence level of the student in the Dwiwarna High School (Boarding School) Parung Bogor. The instruments usend in this research is the emotional intelegence scale. The research subjects are 70 high school students grade XI Dwiwarna High School (Boarding School) Parung Bogor 2019/2020. The research showed that 1,4% students have low emotional intelegence, 82,9% students have average emotional intelegence, and 15,7% students have high emotional intelegence. This research can be used by guidance and counseling teacher to improve student’s emotional intelegence at school using guidance program or counseling service.